2016
DOI: 10.5811/westjem.2016.1.29462
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Cannulation: Time to Bring Subclavian Central Lines Back

Abstract: Despite multiple advantages, subclavian vein (SCV) cannulation via the traditional landmark approach has become less used in comparison to ultrasound (US) guided internal jugular catheterization due to a higher rate of mechanical complications. A growing body of evidence indicates that SCV catheterization with real-time US guidance can be accomplished safely and efficiently. While several cannulation approaches with real-time US guidance have been described, available literature suggests that the infraclavicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…SCV is an alternative to internal jugular vein (IJV) when this is difficult to locate, as in hypovolemic or obese patients 4,5 . SCV cannulation has the advantage of fixed landmarks but may be associated with potentially severe complications, e.g., pneumothorax or hemothorax, likely related to limited operator experience 6 .…”
Section: Introductionmentioning
confidence: 99%
“…SCV is an alternative to internal jugular vein (IJV) when this is difficult to locate, as in hypovolemic or obese patients 4,5 . SCV cannulation has the advantage of fixed landmarks but may be associated with potentially severe complications, e.g., pneumothorax or hemothorax, likely related to limited operator experience 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrates that to use of real-time US guidance for infraclavicular placement of SCV catheters can lead to decreased mechanical complications and improved cannulation success ( 11 ). The alternative cannulations require advanced training and experience ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed that compared to anatomic landmark techniques, ultrasound guidance was associated with 71% reduction in catheter-related complications for internal jugular vein placement. 5 Emerging data also support the use of ultrasound in infraclavicular subclavian vein access. 5,6 Ultrasound would have prevented this complication in our patient.…”
mentioning
confidence: 93%
“…5 Emerging data also support the use of ultrasound in infraclavicular subclavian vein access. 5,6 Ultrasound would have prevented this complication in our patient. However, it was not then performed routinely in our institution.…”
mentioning
confidence: 93%